Skew Detection and Yarns Density Calculation for Woven Fabric (Journal of Fiber Bioengineering and Informatics, 2014)
Automatic identification of fabric structure is a vital research according to the fabric texture. Due tothe skewed phenomenon which is inevitable during the scanning process, Hough transform is utilized forskew detection. Then wavelet filter is proposed to separate warps from wefts to enhance the informationin vertical and horizontal direction, respectively. Finally, the gray projection curve including peaks andvalleys is obtained in warp and weft directions. According to the peaks, the yarns can be located andsegmented apparently and the fabric density could be obtained. Experimental results show that theprecision of skew detection could be controlled within 2° while the accuracy of yarns density detectioncan reach up to 100%, which demonstrate that the proposed method is effective in skew detection andfabric density calculation.